Perbedaan Tingkat Kecemasan Pasien Berdasarkan Usia, Jenis Kelamin, Tingkat Pendidikan dan Pengalaman Pencabutan Gigi Di RSGM FKG Universitas Jember (The Differences Patients Anxiety Level Based on Age, Sex, Education level and Tooth Extraction Experience at Dental Hospital, Faculty of Dentistry, University of Jember) - Syamsul Bachri; Zainul Cholid; Abdul Rochim (Pustaka Kesehatan, 2017)
Tooth extraction is a surgery treatment which involves bone tissue dan soft-tissue structure of oral cavity. The procedure of the tooth extraction causes the highest dental anxiety. Among the factors to affect one’s anxiety level are age, sex, education level, as well as the experience of taking tooth extraction. The objective of this research is to find out the variance of the degree of patient’s anxiety level based on age, sex, education level and tooth extraction experience at Dental Hospital, Faculty of Dentistry, University of Jember. This research used analytical survey design with retrospective approach. The subject of this research is the entire patients who visit the Oral Surgery section toperform tooth extraction during the period of January to March 2016. This research employed consecutive sampling as its sampling collection technique. As many as 86 respondents are taken as the sample of this research. Sample is measured using questionnaire regarding the anxiety level prior the extraction. Results of this research reveal that 49 patients experience anxiety prior to the tooth extraction treatment. Analysis is performed using Mann-Whitney statistics, resulting in the value of 0,903 and 0,334 (p>0,05), while the Kruskall Wallis testing demonstrates the value of 0,004 and 0,001 (p<0,005). The conclusion of this research states that the variance among the patients’ anxiety level based on age and education level exist. Meanwhile, regarding similar level of anxiety, sex and the experience of tooth extraction at the Dental Hospital University of Jember do not exist, respectively.Keywords: Tooth extraction, dental anxiety